2022
DOI: 10.1177/09691413221074803
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of colon capsule endoscopy accuracy for colorectal cancer screening. An alternative during the Covid-19 pandemic?

Abstract: Aim To determine the diagnostic accuracy of colon capsule endoscopy for colorectal cancer screening. Methods Studies that compared the diagnostic performance of colonoscopy and second-generation colon capsule endoscopy (CCE-2) for screening of asymptomatic patients aged 50–75 years were included. The primary outcomes were sensitivity, specificity, and positive and negative likelihood ratios for polyps and adenomas measuring at least 6 mm or 10 mm. Results Eight full-text studies that evaluated 1602 patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“… 32 Colon capsule endoscopy has also been advocated as an alternative for CRC screening after a positive FIT, as it can be performed as an out-of-clinic procedure, avoiding patients to attend medical facilities, and it has demonstrated a high diagnostic accuracy (area under receiver operating curve 0.963 for polyps at least 6 mm); hence, it may be used to filter patients in need of a colonoscopy. 33 In fact, current CRC screening guidelines recommend this technique as a valid alternative for individuals unable or unwilling to undergo colonoscopy. 34 Computed tomography colonography is also recommended in this setting.…”
Section: Impact Of Covid-19 Pandemic In Crc Screeningmentioning
confidence: 99%
“… 32 Colon capsule endoscopy has also been advocated as an alternative for CRC screening after a positive FIT, as it can be performed as an out-of-clinic procedure, avoiding patients to attend medical facilities, and it has demonstrated a high diagnostic accuracy (area under receiver operating curve 0.963 for polyps at least 6 mm); hence, it may be used to filter patients in need of a colonoscopy. 33 In fact, current CRC screening guidelines recommend this technique as a valid alternative for individuals unable or unwilling to undergo colonoscopy. 34 Computed tomography colonography is also recommended in this setting.…”
Section: Impact Of Covid-19 Pandemic In Crc Screeningmentioning
confidence: 99%
“…For people with no risk factors, screening starts at age 50-years-old. People with a close relative (parent or sibling) with colorectal cancer or polyps will start screening at age 40-years-old or at 10 years before the youngest age at which a relative was diagnosed[ 7 , 20 - 27 ]. These patients will often undergo screening every 5 years, even if their test is normal.…”
Section: Screening and Surveillance For Colorectal Cancermentioning
confidence: 99%
“…These patients will often undergo screening every 5 years, even if their test is normal. Less common types of inherited colon cancer (hereditary non-polyposis colon cancer and familial adenomatous polyposis) may require more frequent screening, beginning at a much earlier age[ 7 , 20 - 27 ]. There are various methods of screening as described below.…”
Section: Screening and Surveillance For Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…These studies signaled the markedly improved sensitivity and accuracy of CCE-2 compared to CCE-1. Several subsequent controlled studies have reported the efficacy of CCE-2 in identifying colonic polyps [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: 2nd-generation Colon Capsule Endoscopy and Polyp Detectionmentioning
confidence: 99%